Prevalence of diabetic retinopathy in patients with diabetes mellitus diagnosed after the age of 70 years. Issue 3 (1st March 1997) - Cahill, M; Halley, A; Codd, M; O'Meara, N; Firth, R; Mooney, D; Acheson, R W
Abstract : AIMS/BACKGROUND: A hospital based prevalence study was undertaken to estimate the prevalence of diabetic retinopathy (DR) in patients diagnosed as having diabetes mellitus after the age of 70 years. The prevalence of visually threatening retinopathy at the time of diagnosis of diabetes was also determined. The association between prevalence of DR and duration of diabetes mellitus, mode of treatment, HbA1c levels, presence of hypertension, and sex of patient was examined and a comparison was drawn between this study and earlier prevalence studies of DR in older type II diabetics. METHODS: Using data on the Irish Diabetic Retinopathy Register located in the Mater Misericordiae Hospital, Dublin, all patients who were diagnosed as having type II diabetes mellitus after the age of 70 years were invited to attend for ophthalmic review. Medical records were examined to determine the duration of diabetes mellitus, mode of treatment, recent HbA1c levels, and the presence of systemic hypertension. RESULTS: Of the 150 patients examined, 21 (14%) had some form of DR and 10 of these patients (6.6%) had visually threatening retinopathy or previously treated visually threatening retinopathy. Five patients (3.3%) presented with visually threatening retinopathy at the time of diagnosis of diabetes. Those patients with DR had a significantly higher median duration of diabetes (5.0 years) compared with those patients without DR (3.5 years). A significantly higher proportion of patients with DR required treatment with insulin and a correspondingly lower proportion of patients without DR were controlled on diet alone. There was no significant association between prevalence of DR and HbA1c levels, systemic hypertension, or sex of patient. There was a lower overall prevalence of DR in comparison with earlier studies. CONCLUSIONS: The prevalence of DR in these elderly type II diabetics is lower than that previously reported in patients with type II disease but a small percentage of patients had visually threatening retinopathy at presentation. Longer duration of diabetes and insulin use were associated with a significantly increased prevalence of DR. All elderly type II diabetic patients require thorough ophthalmic examination near to the time of first presentation and thereafter at regular intervals.